KAWASAN EKONOMI KHUSUS DAN POTENSI PARIWISATA PROVINSI KEPULAUAN BANGKA BELITUNG - Cipta, Hendra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
Special Economic Zone is a program that supports the acceleration of Indonesia's economic development and tourism into one of the sectors included in the Special Economic Zone. Bangka Belitung Islands Province is a beautiful province and rich in natural resources to serve as a tourism destination. With good planning and management of the Province of Bangka Belitung Islands can be a tourism destination that is taken into account by tourists in the country and abroad.